Evaluation of Sorption Capacity of Scrap Tyre in the Removal of Copper (II) Ion from Aqua System (Biological Sciences - PJSIR, 2006)
The use of scrap-tyre (ST), which was both a waste and pollutant was investigated as a low-cost sorbent to sorbed Cu (II) from aqueous solution. The influence of pH, sorbent dosage, contact time, and initial sorbate concentra- tion on the uptake of Cu (II) by ST were studied. Optimum sorption of Cu (II) by ST was achieved at pH 6. The amount of sorbate sorbed per gram of sorbent decreased with increase in sorbent dosage. Maximum uptake of the Cu (II) was achieved within the first thirty minutes of contact between the ST and the Cu (II). The equilibrium relationship between the concentration of the Cu (II) in the fluid phase and the concentration in the ST particles at a given tempera- ture showed that the sorption mechanism was like adsorption rather than distribution into any phase. Analysis of the results using Langmuir and Freundlich models showed that it conformed to Langmuir equation based on the formation of a monomolecular layer. The adsorption capacity due to monolayer coverage was 12.95 mg/g, while the energy of adsorption was 3.95 dm/mg.